Hybrid magneto-plasmonic liposomes for multimodal image-guided and brain-targeted HIV treatment - Tomitaka, Asahi (Nanoscale, 2017)
Image-guided drug delivery is an emerging strategy in the field of nanomedicine. Addition of image guidance to traditional drug delivery system is expected to achieve highly efficient treatment by tracking the drug carriers in body and monitoring their effective accumulation in the targeted tissues. In this study, we developed multifunctional magneto-plasmonic liposomes (MPLs), a hybrid system combining liposomes and magneto-plasmonic nanoparticles for a triple-modality image-guided drug delivery. Tenofovir disoproxil fumarate, an antiretroviral drug used to treat Human immunodeficiency virus type 1 (HIV-1) was encapsulated into the MPLs to enable the treatment in the brain microenvironment, which is inaccessible by most of the drugs. We found strong negative and positive contrasts originated from magnetic core of MPLs in magnetic resonance imaging (MRI) and magnetic particle imaging (MPI), respectively. The gold shell of MPLs showed bright positive contrasts in X-ray computed tomography (CT). MPLs achieved to enhance transmigration across an in vitro blood–brain barrier (BBB) model by magnetic targeting. Moreover, MPLs provided desired therapeutic effects against HIV infected microglia cells.